Navigating Complexity in Big History
XV, 525 p. 88 illus., 74 illus. in color.
Keywords: This book explores periodization in Big History against the background of complexity growth across the Universe, on our planet, and in biological, social, and cultural systems. It traces the accelerating rise in complexity throughout history and the major historical transformations involved in the evolution of life, humans, and civilization. It draws on concepts from physics and evolutionary biology to offer potential models of the underlying mechanisms driving this acceleration, along with potential clues to how it might end. In the editors’ introduction (Chapter 1), the effort to periodize is placed within the historical context along with considerations from complexity science. Subsequent chapters explore various aspects of periodization and complexity by (a) identifying symmetrical cosmic and biosocial trends, (b) testing rigor and criteria for evaluating periodization, (c) attempting to integrate different approaches through multiple perspectives, (d) proposing different strategies for determining geometric patterns in terrestrial bio-social evolution, and (e) applying the traditional threshold model to gain insights into possible future pathways. A concluding chapter identifies commonalities, research gaps, and possible approaches to integration as the current state of the world system rapidly evolves, while also offering a deeper understanding of complexity dynamics and historical processes. Each chapter includes an extensive bibliography, allowing a deeper and more detailed examination of the issues covered.